2012
DOI: 10.7314/apjcp.2012.13.9.4763
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 5 Agonism Protects Mice from Radiation Pneumonitis and Pulmonary Fibrosis

Abstract: Radiation pneumonitis and pulmonary fibrosis are the main complications with radiotherapy for thoracic neoplasms, directly limiting the efficient dose in clinical application and currently there are few medicines that effectively function as radioprotectants. However, a TLR5 agonist, CBLB502, was confirmed to have protective efficacy against hematopoietic and gastrointestinal radiation syndromes in mice and primates. This study points to a new direction for protection against thoracic radiation-induced pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 12 publications
0
22
0
1
Order By: Relevance
“…Albeit developments in radiotherapy techniques, such as the Three-Dimensional Conformal Radiation Therapy (3DCRT) and the IntensityModulated Radiation Therapy (IMRT), which offer greater protection to adjacent healthy tissues and, at the same time, increase the dose absorbed by the tumour target, the frequency of RP has not been eliminated (Bucci et al, 2005;Tsoutsou and Koukourakis, 2006;Guckenberger et al, 2010). Although, some inflammatory mediators such as amifostine (Kouvaris et al, 2007) or Toll-like receptor agonism (Wang et al, 2012) have shown evidence of radioprotection in vitro and in vivo studies, RP clearly remains a radiation dosimetric-related morbidity (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Albeit developments in radiotherapy techniques, such as the Three-Dimensional Conformal Radiation Therapy (3DCRT) and the IntensityModulated Radiation Therapy (IMRT), which offer greater protection to adjacent healthy tissues and, at the same time, increase the dose absorbed by the tumour target, the frequency of RP has not been eliminated (Bucci et al, 2005;Tsoutsou and Koukourakis, 2006;Guckenberger et al, 2010). Although, some inflammatory mediators such as amifostine (Kouvaris et al, 2007) or Toll-like receptor agonism (Wang et al, 2012) have shown evidence of radioprotection in vitro and in vivo studies, RP clearly remains a radiation dosimetric-related morbidity (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Delivery of entolimod prior to and shortly after radiation has been demonstrated to protect mice and rhesus monkeys from lethal total body irradiation, with radiation-induced damage to both hematopoietic and GI tissues being reduced and tissue repopulation being enhanced [22]. Additionally, treatment with entolimod has been documented to reduce the severity of radiation-induced pneumonitis and pulmonary fibrosis [23]. Entolimod does not appear to radioprotect tumor tissue, and it has been documented to be well tolerated by patients in clinical trials.…”
Section: • • Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 96%
“…Results from clinical trials on prevention of radiation pneumonitis have not been definitive [4,[19][20][21] Inhibitors of apoptosis Entolimod Suppression of apoptosis through activation of NF-κB Entolimod protects against lethal total body irradiation in mice and primates [22,23] ACE: Angiotensin-converting enzyme; ROS: Reactive oxygen species; SOD: Superoxide dismutase. Redox homeostasis within a cell is maintained in part by a series of antioxidant enzymes that include glutathione peroxidase, catalase and superoxide dismutase (SOD).…”
Section: Nitroxidesmentioning
confidence: 99%
“…Therefore, potential side effects of RT should be observed during and after the treatment. Among these side effects,the most important and dose-limiting one is the radiation pneumonia (RP) (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%